The mitochondrial function of peripheral blood cells in cognitive frailty patients - Qin, Li; Huang, Tingting; Zhang, Danmei; Wei, Liqin; Li, Guochao; Zhu, Qianqian; Tong, Qiangwei; Ding, Guoxian; Liu, Juan (Frontiers in Aging Neuroscience, 2024)
BackgroundCognitive frailty (CF), characterized by the coexistence of physical frailty and cognitive impairment, is linked to increased morbidity and mortality in older adults. While CF has been linked to multiple physiological and lifestyle factors, the underlying biological mechanisms remain poorly understood. This study investigated the risk factors for CF and explored the relationship between mitochondrial function and CF in hospitalized patients.MethodsA total of 279 hospitalized individuals were recruited from December 2020 to August 2022, conducted comprehensive clinical assessments, and collected peripheral blood samples. CF was evaluated using the Physical Frailty Phenotype and Montreal Cognitive Assessment scales. Nutritional status was assessed with the Mini Nutritional Assessment, and depression was measured using the Geriatric Depression Scale. DNA was obtained from the peripheral blood and interrogated for mitochondrial DNA copy number (mtDNAcn). Peripheral blood mononuclear cells isolated from peripheral blood were examined for respiratory function and reactive oxygen species (ROS) levels. Additionally, plasma samples were analyzed for inflammatory markers and Carnitine Palmitoyltransferase II (CPT2).ResultsAmong the participants, 90 were classified as CF and 46 as non-CF. Logistic regression analysis revealed that increased age (OR 1.156, 95% CI 1.064–1.255), lower educational attainment (OR 0.115, 95% CI 0.024–0.550), malnutrition (OR 0.713, 95% CI 0.522–0.973), and higher depression scores (OR 1.345, 95% CI 1.065–1.699) were significantly associated with CF. The independent t tests and Mann–Whitney U tests showed the CF group exhibited impaired mitochondrial function, characterized by reduced mtDNAcn and respiratory activity, coupled with elevated ROS, interleukin-6, and CPT2 levels compared with the non-CF group. After adjusted for age, sex, and BMI, compared with non-CF group, the OR values for the CF group of mtDNAcn and ROS were 0.234 (95% CI = 0.065–0.849) (p = 0.027) and 1.203 (95% CI = 1.075–1.347) (p = 0.001), respectively. The Sensitive analysis showed that the area under curve values for mtDNAcn and ROS were 0.653 and 0.925.ConclusionAge, lower educational attainment, malnutrition, and depression are significant risk factors for CF. Moreover, mitochondrial dysfunction, characterized by decreased mtDNAcn, impaired respiratory function and increased ROS levels appears to be a critical phenotype of CF.